Investigating the Students' Method in Writing English Academic Essay - Octafeani, Elsy; Zasrianita, Fera; Revola, Yashori (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to investigate the methods used by students in writing academic essays in English. This research is motivated by the importance of academic essays writing skills in the context of higher education, particularly in English as an international language. This study used a qualitative approach with a case study method, involving several English language study program students as participants. Data were collected through in-depth interviews, observations of the writing process, and analysis of written essay documents. The results showed that students used various methods in the writing process, such as brainstorming, outlining, drafting, and revising. However, there were significant differences in the effectiveness of each method used, depending on linguistic background, previous writing experience, and understanding of academic essay structure. This study concluded that structured training and ongoing guidance are essential to systematically improve students' academic essays writing skills. These findings are expected to serve as a reference in developing academic essays, writing curricula, and teaching strategies in higher education.